Godspell [videorecording (DVD)] : a musical based on the Gospel according to St. Matthew - Greene, David, 1921-2003; Garber, Victor; Haskell, David; Thigpen, Lynne; Schwartz, Stephen (Columbia Tristar Home Video, 2007)
Film adaptation of the off-Broadway musical based on the Gospel According to St. Matthew. "Set in contemporary New York City, John the Baptist gathers a diverse band of youthful disciples to follow and learn from the teachings of Jesus. They form a roving acting troupe that enacts the Parables through the streets and landmarks of ... New York City"--Container.